2016
DOI: 10.1021/acs.jpclett.5b02851
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Water Delivery to the Active Site of Photosystem II along the S2 to S3 Transition

Abstract: The two water molecules serving as substrate for the oxygen evolution in Photosystem II are already bound in the S2 state of the Kok-Joliot's cycle. Nevertheless, an additional water molecule is supposed to bind the cluster during the transition between the S2 and S3 states, which has been recently revealed to have the Mn4CaO5 catalytic cluster arranged in an open cubane fashion. In this Letter, by means of ab initio calculations, we investigated the possible pathways for the binding of the upcoming water mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
94
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 40 publications
14
94
2
1
Order By: Relevance
“…Substrate analogues are instead found either on Mn4 or at the endpoint of the O4 channel, implying that this channel may be the only one involved in substrate delivery and that Mn4 may be the only site involved in substrate binding. This is consistent with recent studies of the S 2 –S 3 progression, 73,134,142,148 which showed that the first component of the S 3 state is a “closed-cubane” structure with a five-coordinate Mn4( iv ) center. 73 The approximately trigonal bipyramidal geometry of the Mn4( iv ) site of this species results in properties such as absorption in the near-IR and high zero-field splitting, 73 similarly to analogous synthetic Mn( iv ) complexes.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Substrate analogues are instead found either on Mn4 or at the endpoint of the O4 channel, implying that this channel may be the only one involved in substrate delivery and that Mn4 may be the only site involved in substrate binding. This is consistent with recent studies of the S 2 –S 3 progression, 73,134,142,148 which showed that the first component of the S 3 state is a “closed-cubane” structure with a five-coordinate Mn4( iv ) center. 73 The approximately trigonal bipyramidal geometry of the Mn4( iv ) site of this species results in properties such as absorption in the near-IR and high zero-field splitting, 73 similarly to analogous synthetic Mn( iv ) complexes.…”
Section: Resultssupporting
confidence: 93%
“…73 The approximately trigonal bipyramidal geometry of the Mn4( iv ) site of this species results in properties such as absorption in the near-IR and high zero-field splitting, 73 similarly to analogous synthetic Mn( iv ) complexes. 149151 These studies established that water binding can only occur at this S 3 -state species: water is delivered via the O4 channel to the Mn4 center and binds via a low-barrier transition state, 73,148 allowing access to the other components of the S 3 state. 71 Based on the above, we propose that occupation of the W6 site by methanol may enhance the S 3 population with the five-coordinate Mn( iv ) ion by inhibiting water delivery to the Mn4 site.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This was supported further by the very slow reaction of S 3 with reductants like hydrazine or hydroxylamine as compared to that with S 2 state (Messinger et al 1991;Messinger and Renger 1990). At present, it appears that this structural change is relatively minor with regard to Mn-Mn and Mn-Ca distances, but may involve the binding of one water molecule to the Mn 4 CaO 5 cluster (Noguchi 2008;Suzuki et al 2008;Siegbahn 2009)-possibly in a complex sequence of events (Cox and Messinger 2013;Siegbahn 2013;Retegan et al 2016;Capone et al 2016;Ugur et al 2016). We note though that substrate water exchange experiments exclude the water molecule binding to the Mn 4 CaO 5 cluster, during this transition, to act as a Fig.…”
Section: Gernot's Legacymentioning
confidence: 96%